2013
DOI: 10.1111/pde.12093
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Tinea Capitis in an Irish Pediatric Population and a Comparison of Scalp Brushings Versus Scalp Scrapings as Methods of Investigation

Abstract: A retrospective study of 391 children with suspected tinea capitis was analyzed to examine the prevalence of dermatophyte species and to compare the efficacy of the scalp scraping method with that of the hairbrush method for diagnoses over a 6-year period. Trichophyton tonsurans tinea capitis is the most common pathogen. The hairbrush method of obtaining specimens for fungal culture was superior to scalp scrapings (p = 0.03) in making the diagnosis, and using two methods (p < 0.001) increased the yield of iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 4 publications
2
17
0
3
Order By: Relevance
“…have demonstrated that gauze swabs make an equally effective and often more convenient sampling method. A comparison of sampling methods for the detection of dermatophytes in asymptomatic carriage has been described . This suggests that multiple sampling methods, such as a scalp scraping and a brush, are likely to lead to an increased yield of dermatophyte fungus from infected scalps .…”
Section: Laboratory Diagnosis Of Tinea Capitismentioning
confidence: 99%
“…have demonstrated that gauze swabs make an equally effective and often more convenient sampling method. A comparison of sampling methods for the detection of dermatophytes in asymptomatic carriage has been described . This suggests that multiple sampling methods, such as a scalp scraping and a brush, are likely to lead to an increased yield of dermatophyte fungus from infected scalps .…”
Section: Laboratory Diagnosis Of Tinea Capitismentioning
confidence: 99%
“…Apart from skin scrapings, samples include hair roots in case of suspected tinea capitis and nail clippings in case of suspected onychomycosis (Table ). Particularly in tinea capitis caused by anthropophilic dermatophytes, primarily T. tonsurans , the hairbrush method is significantly superior to scalp scraping (Table ) . ­Immediately after brushing scalp and hair, the brush is gently pressed directly onto the agar plate.…”
Section: Mycologic Lab Diagnosticsmentioning
confidence: 99%
“…The animals may harbor the pathogen in their fur without showing clinical signs (asymptomatic carriers) [5]. Studies conducted in various European countries [7][8][9][10][11][12][13][14][15][16][17][18][19] have suggested a pathogen shift, showing a steady increase in the percentage of TC cases being caused by anthropophilic species (M. audouinii, T. tonsurans, T. violaceum, T. soudanense). In addition to the other two zoophilic dermatophytes -Trichophyton (T.) mentagrophytes and T. verrucosum -that play an important role in TC, T. benhamiae too has become an increasingly relevant pathogen in central parts of Germany and elsewhere [6].…”
Section: Pathogens and Transmissionmentioning
confidence: 99%
“…In lesions characterized by only minimal inflammation, scales and hairs can be collected using either the blunt end of a scalpel or by using the brush-culture or the swab method. A retrospective study [16] revealed the brush method to be statistically significantly superior to the scalpel method in terms of collecting material for pathogen detection; however, the highest sensitivity was achieved with a combination of both methods. The number of "positive" indentations subsequently allows for a rough quantification [45].…”
Section: Samplingmentioning
confidence: 99%
See 1 more Smart Citation